The Effect of Star Fruit Leaf Boiled Water on Changes in Blood Pressure in Elderly People With Hypertension In Sooko Village, Mojokerto Regency - Mustika Sari, Surya; Vidia Effendy, Henny (Universitas Islam Lamongan, 2023)
The high prevalence of elderly people with hypertension is one of the problems that affect the degree of public health. Lifestyle, family history, race, age, gender, obesity, stress and attitude are factors that spur the onset of hypertension. One of the efforts made to overcome the problem non-pharmacologically by giving boiled water to star fruit leaves. This study aims to determine the effect of star fruit leaf boiled water on changes in blood pressure in hypertensive patients in Sooko Village, Mojokerto Regency. The design of this study is Quasy Experiment Pre Test – Post Test With Control Group Design. The elderly population of people with hypertension in Sooko Village, Mojokerto Regency was 45 respondents, the sample size in this study amounted to 40 respondents and was divided into two groups, namely treatment and control, with purposive sampling techniques. The data obtained through the blood pressure observation sheet was then analyzed using the paired sample T-Test. The results showed that there was a change in blood pressure Pre Test Post Test. The average value of MAP Pre treatment was 115.10 mmHg and control 116.10 mmHg. In the Post Test, the average value of MAP Post treatment group was 105.10 mmHg and the control group was 118.46 mmHg. The results of the static test study were obtained on average from the pre-test and post-test groups ( P = 0.000<α = 0.05)